A Review on Fucoidan Structure, Extraction Techniques, and Its Role as an Immunomodulatory Agent - Thilina U. Jayawardena; D. P. Nagahawatta; I. P. S. Fernando; Yong-Tae Kim; Jin-Soo Kim; Won-Suk Kim; Jung Suck Lee; You-Jin Jeon (Marine Drugs, 2022)
Functional ingredients for human health have recently become the focus of research. One such potentially versatile therapeutic component is fucose-containing sulfated polysaccharides (FCSPs), referred to as fucoidans. The exploitation of marine brown algae provides a rich source of FCSPs because of their role as a structural component of the cell wall. Fucoidans are characterized by a sulfated fucose backbone. However, the structural characterization of FCSPs is impeded by their structural diversity, molecular weight, and complexity. The extraction and purification conditions significantly influence the yield and structural alterations. Inflammation is the preliminary response to potentially injurious inducements, and it is of the utmost importance for modulation in the proper direction. Improper manipulation and/or continuous stimuli could have detrimental effects in the long run. The web of immune responses mediated through multiple modulatory/cell signaling components can be addressed through functional ingredients, benefiting patients with no side effects. In this review, we attempted to address the involvement of FCSPs in the stimulation/downregulation of immune response cell signaling. The structural complexity and its foremost influential factor, extraction techniques, have also attracted attention, with concise details on the structural implications of bioactivity.